Relationships between parental attachment, peer attachment and stress among school-going adolescents in Akwa Ibom state Nigeria - Abia, Edidiong Maurice; Hasbullah, Muslihah; Daud, Mohd Najmi (Human Resource Management Academic Research Society, 2022)
Parent-adolescent relationship has been viewed as a crucial factor in the outcome of stress among adolescents. In addition to the stressors in home environment, school-going adolescents spend most of their waking hours within the school environment which also potentially contribute to stress. Empirical investigation has been very scanty with regards to the relationships among stress, parental and peer attachments among school-going adolescents in Nigeria. This study was a cross-sectional survey which drew participants, using a stratified random sampling technique, from three senatorial zones of Akwa Ibom state in Nigeria. Data were collected using a standardized, reliable and valid measures of the study variables among the 372 school-going adolescents. Results showed that parental attachment (r = -.107, p<.05) and peer attachment (r = -.190; p<.01) were significantly associated with stress. Results also indicated that parental attachment and peer attachment, significantly predicted stress. Peer attachment was found to be the strongest predictor of stress (?= -.24, p< .01). Practically, the study offered parents/guardians, home managers and educational institutions useful suggestions on reducing and mitigating the effects of stress. Stress reduction through healthy parental and peer attachment can be enhanced by organizing school-based psycho-educational with focus on parental and peer attachment.